2023
DOI: 10.1093/ced/llad255
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT-3.5 and ChatGPT-4 dermatological knowledge level based on the Specialty Certificate Examination in Dermatology

Abstract: Background The global use of artificial intelligence has the potential to revolutionize the healthcare industry. Despite the fact that artificial intelligence is becoming more popular, there is still a lack of evidence on its use in dermatology. Objective The study aimed to determine the capacity of ChatGPT-3.5 and ChatGPT-4 to support dermatological knowledge and clinical decision-making in medical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…When our results are placed alongside studies from other disciplines that have examined ChatGPT's performance on single-answer and multiple-choice questions, we observe a similar trend -a roughly 20% performance improvement with ChatGPT 4 over ChatGPT 3.5 [6,[23][24][25]. Studies in otolaryngology, closely related to audiology, have also shown lower performance scores for ChatGPT 3.5, supporting our findings of improved outcomes with the newer version [26,27].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…When our results are placed alongside studies from other disciplines that have examined ChatGPT's performance on single-answer and multiple-choice questions, we observe a similar trend -a roughly 20% performance improvement with ChatGPT 4 over ChatGPT 3.5 [6,[23][24][25]. Studies in otolaryngology, closely related to audiology, have also shown lower performance scores for ChatGPT 3.5, supporting our findings of improved outcomes with the newer version [26,27].…”
Section: Discussionsupporting
confidence: 83%
“…Presently, two versions of ChatGPT are accessible to the general public: the freely available ChatGPT 3.5, based on an earlier LLM, and the more advanced, subscription-based ChatGPT 4. Research has shown that ChatGPT 4 outperforms its predecessor, demonstrating superior accuracy in various fields such as dermatology, where it achieved 80-85% accuracy compared to 60-70% for ChatGPT 3.5 [6]. Similar improvements are observed in orthopedic assessments and in general medical examinations, with ChatGPT 4 consistently outperforming ChatGPT 3.5 [7,8].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…While ChatGPT-4 demonstrates proficiency in conducting general conversations in multiple languages, its capacity for medical reasoning and understanding remains to be thoroughly assessed. Several studies have indicated ChatGPT’s competence in executing single medical task commands, such as answering multiple-choice questions from exams like the United States Medical Licensing Exam [ 5 , 6 ] and various medical specialty exams [ 6 ]. However, ChatGPT-4 struggles with logical questions [ 7 ] and occasionally fabricates responses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While ChatGPT can carry on general conversations in multiple languages, its ability to reason and understand the language of medicine needs further evaluation. Multiple studies show that ChatGPT does well on single medical task commands such as answering multiple-choice examination questions such as the United States Medical Licensing Exam (5,6) and medical specialty exams (6). However, ChatGPT needs help with logical questions (7) and tends to fabricate answers (8).…”
Section: Introductionmentioning
confidence: 99%